Obligatoryjne określniki źródła wiedzy w językach naturalnych i ich epistemologiczne konsekwencje - Łukasiewicz, Elżbieta (Filozofia Nauki, 2014)
The paper is concerned with evidentials, i.e. information-source markers, in natural languages and their influence on our cognition, communication, and justification of our beliefs. In the first part, we present the functioning of different systems of evidentials in the world's languages and discuss in brief how the grammatical structure of different non-Indo-European languages compels their speakers to code the source of information (visual perception, non-visual sensory perception, inference, hearsay, etc.) in practically every declarative sentence. The second part of the paper addresses the issue of how some epistemological ideas connected with the problem of justification of our beliefs, such as internalism, externalism, justified basic beliefs, and epistemology of testimony, could be reinterpreted in the light of obligatory grammatical evidentiality.